Genetic Markers for Resistance to Gastrointestinal Parasites in Sheep and Goats from the Southern Region of the United States: AN383/AN383, 01/2022 - Estrada Reyes, Zaira Magdalena; Tsukahara, Yoko; Goetsch, Arthur L.; Gipson, Terry A.; Sahlu, Tilahun; Puchala, Ryszard; Mateescu, Raluca G. (EDIS, 2022)
This publication discusses a research project designed to explore the genetics of resistance to gastrointestinal parasites in sheep and goats. Written by Zaira M. Estrada Reyes, Yoko Tsukahara, Arthur L. Goetsch, Terry A. Gipson, Tilahun Sahlu, Richard Puchala, and Raluca G. Mateescu, and published by the UF/IFAS Department of Animal Sciences, January 2022.